Pengukuran Status Gizi : Perbedaan BB dan TB Saat Konsumsi Makanan Bergizi Gratis - Rani Kawati Damanik; Sri Dearmaita Purba; Antonij Edimarta Sitanggang; Taruli Rohana Sinaga; Veronika Agustin Purba (-, 2026)
Nutritional status is an important indicator used to assess a child's health and growth. Good nutritional status supports physical growth and cognitive development, as well as increasing a child's resistance to various diseases. The Community Service program aims to measure nutritional status: the difference between weight and height during consumption of free nutritious food. The Community Service program includes a preparatory stage, including a location survey, which includes a preliminary survey of beneficiaries of the free nutritious food program in the Dwi Kora sub-district of Medan. The implementation stage includes the provision of free nutritious food to children. The evaluation stage involves measuring children's height and weight. Descriptively, there was an increase in average height from 112.56 cm to 113.67 cm and an increase in average weight from 17.56 kg to 17.90 kg between November 2025 and May 2026. Parents are advised to provide nutritious food to their children to meet their nutritional needs and create a future golden generation.